WORKSHOP PEMANFAATAN SOFTWARE MENDELEY SEBAGAI ALAT BANTU PENGELOLAAN REFERENSI SKRIPSI MAHASISWA - Hermansyah Hermansyah; Ana Merdekawati; Nurhairunnisah Nurhairunnisah; I Gusti Made Sulindra; I Made Sentaya; Ardiyansyah Ardiyansyah (KARYA: Jurnal Pengabdian Kepada Masyarakat, 2022)
The difficulties that students feel when starting to compile their final project are the biggest obstacles in completing their obligations, especially in finding references and managing references. The writing and management system is still manual by copying and typing one by one, this has an impact on the length of the process in completing the final task in this case the thesis. To solve these problems, workshops on the use of technological advances were held because nowadays technological advances can be used to make it easier to solve these problems. One of them is by using Mendeley for managing and citing student thesis references. The purpose of this activity is to assist students in managing and citing references more easily and making thesis work time efficient. This activity was held by the Student Representative Council of the Faculty of Teacher Training and Education (FKIP) of Samawa University as a form of their concern for the problems experienced by final semester students. Lectures, practice, and question-and-answer methods are used to convey material during the activity. This activity received a positive response from students who have been experiencing difficulties in preparing their thesis.